Processing and judgment of public accountability by parliament: a performance evaluation applied to the case of Goiás - Velasco, Lucas Cavalcanti (Universidad Nacional del Litoral, 2021)
In the context of Goiás, the results of the processing of the judgment of public accounts by the parliament under a quantitative perspective are investigated. The main hypothesis is that, although the reports are technically ratified, the Legislative Assembly of the State of Goiás does not adopt more consistent political measures to enforce the determinations and recommendations of the Court of Auditors. Academic performance evaluation studies underpin the theoretical approach of research. If for specialized literature the legislative and supervisory functions are equivalent, parliament would relegate the jurisdictional activity of external control to the background. In the discussion, this possibility is pointed out as an institutional and political weakening of the parliament based on the results of indicators constructed for this study.